Post-harvest practices and loss assessment in tomato (Solanum lycopersicum L.) in Kathmandu, Nepal - Tiwari, Injila; Shah, Kabita Kumari; Tripathi, Subina; Modi, Bindu; Shrestha, Jiban; Pandey, Hari Prasad; Bhattarai, Bishnu Prasad; Rajbhandari, Binayak Prasad (Journal of Agriculture and Natural Resources, 2020)
Postharvest loss is one of the major problems in tomato production. This study was conducted to assess the post-harvest practices and losses of tomato at the farmers’ fields in three districts namely Kathmandu (Kavresthali), Lalitpur (Lubhoo, and Lamatar), and Bhaktapur (Tathali and Kaushaltar). By using a simple random sampling method, the sample size of 60 respondents was chosen. A pre-tested questionnaire, group conversation, and key-informant survey were applied in this study. The results revealed that 10.3% of the respondents produced the tomato on a small scale whereas 58.8% of respondents produced on large scale. 10% of total losses were found from harvesting to marketing. In the field, during harvesting and packaging, there was a 2% loss. The tomato loss was negligible during grading and washing. 4% loss was found during the transportation of tomato and 2% of the loss during the storage of tomato. To the producer level, the insufficient knowledge about the storage, packaging, transportation, and random harvesting led to the maximum loss of tomato. In the study area, the producers played important role in reducing the postharvest loss of tomato, therefore, public awareness should be increased through mass media about the proper harvesting and storing of tomato.